THE CROP AND IT ROLE IN TAKING DECISIONS - Mihăilă, Marius-Florin (International Journal of Legal and Social Order, 2024)
„The crop that comes from the Latin word ‘colere’ that is translated ‘to grow/‘to honor’ generally only human activity. The definition given by UNESCO considers culture as <<a number of distinc characterstics of a society or terms like social grup in spiritual, materials, intellectuals or emotional.>>. Culture is an inheritance which is transmitted by means of specific communication codes such as gestures, words, writingand arts, media (press, radio, television), interactive media (phone). In the same way, the gestures, rituals, theoretical knowledge, abstract norms, religon are transmitted. Culture can be acquired through varous forms of subjective memory (reflexes, words, images), but olso through objectue memory (objets, landscapes, books, numbers, rules).